(untitled) (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2023)
This PKM activityÂ already implementedÂ in Borong Village, Herlang District, Bulukumba Regency, South Sulawesi. The location of the partners is an agricultural area with the main occupation of the community as farmers. This PKM activity is focused on solving partner problems related to agricultural activities namely plantation agriculture with the main crop being cocoa. The problem faced by partners is the presence of disease attacks on cocoa plants that have not been resolved which causes production and income to decrease as well as the use of raw materials around the environment to be used as organic fertilizer such as compost and bokashi. The solutions offered to partners are training, mentoring and evaluation related to how to treat cocoa pod disease which until now has not been resolved, Likewise related to the manufacture of organic fertilizers such as compost, bokasi, or the use of manure which comes from his cattle. The dedication results show that Cocoa farmers have been able to make vegetable pesticides from maja fruit, neem leaf extract and has been able to make various types of organic fertilizers such as compost and bokashi